An Analysis of Imperative Sentences in “The Boss Baby 1” Movie Script - Islam, Bangun; Nazri, M. Adib; Surayya, Ayu; Wati, Laila (Innovative: Journal Of Social Science Research, 2024)
This study aims to analyze imperative sentences found in the script of the movie "The Boss Baby 1." Imperative sentences, which serve to give commands, requests, or instructions, play a crucial role in shaping the interactions among characters in the film. The analytical method employed is a qualitative approach, focusing on the identification, classification, and interpretation of the functions and contexts of imperative sentence usage. The analysis results show that imperative sentences are not only used to convey commands but also to create character dynamics and convey moral messages. These findings are expected to provide deeper insights into language usage in the context of media films and enhance understanding of the social interactions depicted in the film's narrative.